Modeling the characteristics of internal soliter wave in sea water using the korteweg de vries equation soliton solution - Yogi Febriano (PILLAR OF PHYSICS, 2014)
Internal soliton wave is the wave that happen below of sea surface. This wave occur is caused by distinction of mass density of seawater layer. The characteristic of this wave is defend it form and velocity. The aim of this research are to study model and analyzed the effect of amplitude, mass density, and thickness of layer towards internal soliton waves velocity. This research analyze equation of Korteweg de Vries of internal soliton wave to get the soliton solution from the result of this research was designed a program using Matlab 7.0. The result of program are an output of velocity and modelling chart in three dimensional. This result shows the effect of amplitude, mass density, and layer thickness towards velocity and widening of wave pulse